Can the emergency department sustain the first strike? Experience from the 2016 earthquake in Tainan. Issue 5 (September 2019) - Yang, I-Ching; Peng, An-Chi; Hsu, Chien-Chin; Chen, Kuo-Tai
Background: After the main shock of a major earthquake, casualties cluster in a short period and may overwhelm the capacities of health care facilities. An earthquake with a magnitude of 6.4 on the Richter scale struck Tainan City causing 117 fatalities and 513 injuries. Objectives: We conducted a retrospective study to review the medical records of emergency department after the attack of earthquake. The aim of this study was delineating the medical resource requirements after the disaster. Methods: We reviewed the medical records of patients admitted to the emergency department of Chi Mei Medical Center. Each chart indicating that the emergency department visit was earthquake-related was reviewed. After the earthquake struck, the Chi Mei Medical Center mobilized off-duty staff through a preset 333 code. Subsequently, routine surgeries and nonurgent admissions were postponed to reserve the maximal capacity for wounded patients. Results: A total of 150 patients were reviewed during the study period. In all, 25 cases (23.8%) required admission, and 9 of them (8.6%) were admitted to the intensive care unit. Patients with earthquake-related injuries constituted 62.8% of all traumatic patients in the 24-h aftermath. The requirements for wound sutures, blood component transfusion, numbers of radiographic/computed tomographic scans, and invasive procedures increased dramatically (earthquake-related/total: 66.0%, 30.0%, 72.1%/57.4%, and 47.7%, respectively). Conclusion: Patients with earthquake-related injuries arrived at the emergency department soon after the earthquake occurred and substantial emergency department resources were utilized in the 24-h aftermath. Each hospital should have a preset mobilization signal to call in off-duty workers to treat casualties resulting from the main shock of an earthquake. Subsequently, hospital-based mobilization should be initiated to provide comprehensive care to severely injured patients.